Exploring mistake of language discourse that arises when learners of Indonesian for Foreign Speakers (BIPA) Fatoni University - Putri, Nia Arya; Tiawati, Refa Lina; Dwinitia, Suci (ppjbsip, 2023)
The purpose of this study is to describe the causes and forms of language errors at the phonological level of BIPA students. This type of research is qualitative research. The method used in this research is descriptive analysis method. The data taken in this study is a form of language error at the phonological level in the form of words spoken by BIPA 1-2 students at Fatoni University Thailand. So. Meanwhile, the data sources in this study were BIPA 1-2 students at Fatoni University, totaling 8 people. The instruments in this study were researchers using laptops and zoom applications and assisted with data inventory formats. Data collection techniques are carried out by observation assisted by recording techniques, observing techniques and note-taking techniques. The technique used in checking the validity of the data in this study is the triangulation technique. The results of data analysis can be concluded several things. First, the forms of language errors found by BIPA students at Fatoni University Thailand at the phonological level are, a) phoneme change errors. b) phoneme omission errors, and c) phoneme additions. Second, the factors causing BIPA students to experience language errors in speaking skills are influenced by factors, first, namely factors influenced by the language they master first. Second, the lack of understanding of the language users of the language they use, many do not understand good and correct Indonesian, both in meaning and in pronunciation or pronunciation.